Youth and Creativity of the Anti-Corruption Movement (Journal of Creativity Student, 2022)
Corruption is a recurring problem in Indonesia. Weak supervision and the lack of efforts to prevent corruption are the reasons why the eradication of corruption in Indonesia is still not successful. Look at the current conditions. Indonesia as a country with the fourth largest population in the world has the potential for both natural resources and human resources. In order to maximize this potential, the leakage of resources through corrupt practices must be suppressed so that these resources can be utilized as much as possible for the benefit of the general public. The size of Indonesia's young generation also needs to be our common concern in efforts to prevent and eradicate corruption. As a candidate for the nation's next generation, anti-corruption values must be instilled in the younger generation in Indonesia. It is intended that in the future Indonesia will become a country free from corruption through the role of the next generation of the nation actively both from within and outside the implementation of government in Indonesia. In addition, prevention efforts for the younger generation in Indonesia so that they are not entangled in corruption are also needed in achieving the goal of eradicating corruption as a whole in the context of creating shared prosperity in Indonesia.